Workplace Diversity and Faculty Performance in a Higher Education Institution in the Philippines - Cantilang, Karen Waniwan (FKIP Universitas Lampung, 2023)
Workplace Diversity and Faculty Performance in a Higher Education Institution. Objectives: This study aimed to identify the relationship between workplace diversity and faculty performance in Eastern Samar State University. Methods: The research employed a quantitative research design utilizing descriptive and correlational approaches. Findings: The results revealed a weak positive correlation between the level of workplace diversity and faculty performance, but the link between the two variables were not found to be significant. The findings of this study suggest that while workplace diversity may have an impact on employee performance, it may not be the only factor in determining performance. Conclusion: This research highlights the importance of organizations to focus on creating a diverse and inclusive workplace. While workplace diversity may have an impact on employee performance, it may not be the only factor in determining performance, therefore there is a need for further studies to explore the relationship between diversity and performance in different contexts.Keywords: diversity, performance, higher education, workplace,correlationDOI: http://dx.doi.org/10.23960/jpp.v13.i2.202327